A potenciális városok egészségügyi infrastruktúrájának és ellátottságának területi sajátosságai - Pál, Viktor (Tér és Társadalom, 1996)
Several works of Hungarian social geography have already dealt with the regional particularities of the system of health care in Hungary, especially with its disequilibria. During the surveys, the most significant regional problems of the Hungarian health care system were very soon explored: A hospital network over-concentrated in certain regions, neglected basic and social care, centralised chronic departments in the hospitals, also, the Budapest-countryside and the village-town dichotomy. This disequilibrium can be seen, apart from the evident differences in the provision of specialised treatments, in the availability of basic health care, as well. Villages too are very likely to demonstrate differences in the levei of development, provision and functions in the health care system. It is even probable, however, that we can fend regional differences in the state of health care between villages at more or less the same levei of development from other aspects, i.e. in villages which can almost be considered as homogeneous. This concept appeared while carrying out a more comprehensive research. To check the appropriateness of this, an individual research method should be elaborated, taking the aspects of comparability into consideration.